ANALYSIS OF THE CONCEPT OF MORAL EDUCATION THOUGHT BUYA HAMKA AS AN EFFORT TO PREVENT BULLYING SELF-STUDY - Arifah, Muthiah; Azzani, Mohammad Zakki (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
Today's education has increasingly seen moral decadence and loss of social values. One of the most urgent is bullying. In line with that, the role of moral education is needed, because morals are the benchmark of a nation both in civilization and progress. Islamic morals are known as akhlaqul karimah, namely noble behavior or morals, namely behavior or character in accordance with the Qur'an and Hadith which are the main sources of religious law. Similar to Hamka's moral education which focuses on reason and akhlaqul karimah. In connection with this, this research is intended to be able to find answers from the analysis of Buya Hamka's moral education thoughts contained in his writings as a preventive effort from bullying behavior. This research was conducted using the library research method or literature study as the basis for this research. Literature studies that become references are from the book 'Philosophy of Life and Akhlaqul Karimah' and other works that intersect with Buya Hamka and the results of previous studies in the form of journals as other sources. Since this is the core of all behavior, the results of studies that provide insight into the virtues of all people are very important for their daily lives. It will be easier for people to get along and develop a great human personality if the origins of this trait are understood, along with the difficulties they face, so that they can place their temperament in the right position. The values that humans develop truly originate from within, and if disturbed, the situations within humans are not much different from how they are dealt with in the human body. Therefore, it is important to understand this in order to find a solution quickly. After that, virtue is used to name the basic nature of all thoughts. 'Iffah, Shaja'ah, 'Adaalah, and Hikmah are these qualities.